O primeiro ciclo da Universidade Federal do Maranhão: uma análise crítica - Tajra, Leda Maria Chaves (1982)
This paper aims at a critical analysis of the 1st cycle the Federal University of Maranhão UFMA, within the context in which it is inserted. State, To achieve this purpose, a historical approach about the University from the creation of in Maranhão State was made, leaving the 1st Colleges in the State of Maranhão until the foundation and functioning of present Universities. This was made in order to just a partial view of the 1st cycle.